Internet and Mobile Phone Addiction. Health and Educational Effects - Lopez-Fernandez, Olatz (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Internet use-related addiction problems (e.g., Internet addiction, problem mobile phone use, problem gaming, and social networking) have been defined according to the same core element: the addictive symptomatology presented by individuals who excessively and problematically behave using the technology. Online activity is the most important factor in their lives, causing them the loss of control by stress and difficulties in managing at least one aspect of their daily life, affecting users' wellbeing and health. In 2018, Gaming Disorder was included as a mental disease in the 11th Revision of the International Classification of Diseases by the World Health Organization. In 2013, the American Psychiatric Association requested additional research on Internet Gaming Disorder. The papers contained in this e-Book provide unique and original perspectives on the concept, development, and early detection of the prevention of these health problems. They are diverse in the nature of the problems they deal with, methodologies, populations, cultures, and contain insights and a clear indication of the impact of individual, social, and environmental factors on Internet use-related addiction problems. The e-Book illustrates recent progress in the evolution of research, with great emphasis on gaming and smartphone problems, signaling areas in which research would be useful, even cross-culturally.